The Investigator’s Actions to Compensate for the Harm Caused by the Crime in Determining the Form of Terminating the Preliminary Investigation - Ivanov, Dmitriy; Potapov, Vasily; Vasyukov, Vitaliy; Artemova, Valeriia; Alimamedov, Elmir (Jurnal Cita Hukum, 2023)
Investigations into the termination of preliminary criminal investigations traditionally encompass two forms: closing a criminal case and concluding the preliminary investigation through an indictment for prosecutor transfer. Prior research has examined these processes, emphasizing the importance of procedural correctness and legal compliance. However, existing studies fall short in elucidating the investigator's actions concerning harm compensation during preliminary investigation termination. The purpose of this study was to explore the investigator's actions to ensure compensation for harm caused by a criminally punishable act during the termination of the preliminary investigation. The authors employed a holistic approach, including the general scientific method, systematic analysis, synthesis, and comparative legal analysis. The results revealed that regardless of the form of termination, measures for compensating victims of criminal acts must be taken. These include appealing against unlawful decisions, and preparing claims for rights protection and compensation in civil proceedings. Compensation for harm remains a priority throughout pre-trial proceedings, even after termination.